Recursive and iterative algorithms for N-ary search problems - Sklyarov, Valery (2006)
The paper analyses and compares alternative iterative and recursive implementations of N-ary search algorithms in hardware (in field programmable gate arrays, in particular). The improvements over the previous results have been achieved with the aid of the proposed novel methods for the fast implementation of hierarchical algorithms. The methods possess the following distinctive features: 1) providing sub-algorithms with multiple entry points; 2) fast stack unwinding for exits from recursive sub-algorithms; 3) hierarchical returns based on two alternative approaches; 4) rational use of embedded memory blocks for the design of a hierarchical finite state machine.